Energy Efficient Homes: An Introduction to Carbon Footprints - Nicholas W. Taylor; Jeffrey Michael; Kathleen C. Ruppert (EDIS)
FCS-3271, a 5-page illustrated fact sheet by Nicholas W. Taylor, Jeffrey Michael, and Kathleen C. Ruppert, introduces the concept of carbon footprint and how it is calculated, including quick facts and a glossary of terms. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.